2017
DOI: 10.1007/s11356-017-9461-z
|View full text |Cite
|
Sign up to set email alerts
|

Health risks of environmental exposure to metals and herbicides in the Pardo River, Brazil

Abstract: Mixture of metals and herbicides in rivers may pose relevant risks for the health of surrounding communities. Humans may be exposed to river pollution through intake of contaminated water and fish, as well as irrigated agricultural products. The aim of this study was to assess the human health risks of environmental exposure to metals and herbicides through water and fish intake in the Pardo River. Metals (Al, As, Be, Cd, Cr, Cu, Pb, Mn, Hg, Ni, Tl, Sn, V, and Zn) were analyzed in river water and in edible fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 41 publications
0
9
0
12
Order By: Relevance
“…However, in water samples, some studies have considerably lower LOQ, such as 0.0007 µg L -1 (Bolea-Fernandez et al, 2015). But most values observed are close to the range (0.04 to 4.00 µg L -1 ), such as 0.21 µg L -1 (Komorowicz and Barałkiewicz, 2016), 0.33 µg L -1 (García-Rico et al, 2019), 0.46 µg L -1 (Kilic et al, 2018) and 0.70 µg L -1 (Machado et al, 2017). In bioindicators, some studies showed values close to those observed in the present data survey, while others showed lower values.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, in water samples, some studies have considerably lower LOQ, such as 0.0007 µg L -1 (Bolea-Fernandez et al, 2015). But most values observed are close to the range (0.04 to 4.00 µg L -1 ), such as 0.21 µg L -1 (Komorowicz and Barałkiewicz, 2016), 0.33 µg L -1 (García-Rico et al, 2019), 0.46 µg L -1 (Kilic et al, 2018) and 0.70 µg L -1 (Machado et al, 2017). In bioindicators, some studies showed values close to those observed in the present data survey, while others showed lower values.…”
Section: Resultsmentioning
confidence: 89%
“…Recent studies have used ICP MS (Bolea-Fernandez et al, 2015;Oroian et al, 2016;Kaya and Turkoglu, 2017;Machado et al, 2017;De La Cruz et al, 2018), HG AAS (Waterlot and Douay, 2015), ET AAS (Hassanpoor et al, 2015; Rev. Bras.…”
Section: Introductionmentioning
confidence: 99%
“…The locals within the riverside use the water for bathing, washing and cooking and therefore could be exposed to the carcinogenic or non-carcinogenic health effects of some heavy metals. Heavy metals such as cadmium, lead and chromium are reported to have both carcinogenic and non-carcinogenic health effects, whereas others such as zinc, aluminum, copper have non-carcinogenic health effects [18,24]. It is therefore extremely important to assess the seasonal exposure risks of the water users for the aforementioned purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Os riscos à saúde humana associados à exposição a contaminantes químicos no ambiente são relevantes no contexto da saúde pública (FLORES et al, 2004;MACHADO et al, 2016). A contaminação da água de rios por herbicidas dificilmente será completamente removida pelo tratamento convencional com a finalidade de abastecimento público (coagulação, floculação, clarificação, filtração e desinfecção), o qual é amplamente utilizado nas estações de tratamento de água brasileiras (MACHADO et al, 2017), e a situação pode ser ainda mais grave em atividades de recreação quando ocorre a ingestão acidental de água do rio.…”
Section: Introductionunclassified
“…Diversos estudos vem sendo realizados para estimar os riscos à saúde humana pela exposição a agentes químicos E microbiológicos em ambientes naturais no Brasil (ALVES et al, 2014;MACHADO et al, 2017;FREGONESI, 2017). No entanto, estudos que avaliem a exposição a herbicidas pela via de ingestão de água durante atividades de recreação ainda são escassos no cenário brasileiro.…”
Section: Introductionunclassified